EFEKTIFITAS MEDIA VIDEO TERHADAP PENGETAHUAN SADARI - Maryuni Maryuni; Irwanti Gustina; Ria Irawan (LPPM Universitas Abdurrab, 2022)
Data from the Global Burden of Cancer (GLOBOCAN) released by the World Health Organization (WHO) states that the number of cases and deaths from cancer until 2018 was 18.1 million cases and 9.6 million deaths in 2018. This study aims to determine the effectiveness of health education for adolescents aged 15-20 years with video media on Knowledge of Breast Self-Examination The method used in this study was the Quasi-Experimental method, the quasi-experimental design used was